One year experience using mycobacterial blood cultures to diagnose tuberculosis in patients with prolonged fever in Vietnam. - Nguyen, D; Nguyen, T; Dao, T; Nguyen, LT; Horby, P; Nguyen, K; Wertheim, H (Journal of Infection in Developing Countries, 2014)
INTRODUCTION: To evaluate the use of mycobacterial blood cultures (MBC) in diagnosing tuberculosis (TB) in patients with prolonged fever admitted to a Vietnamese referral hospital. RESULTS: MBCs from 94 patients (66% male; median age 33 years; 75% HIV positive) were evaluated: 14 were mycobacterium positive (all HIV positive), and MBC was the only positive specimen in 9 cases (41%). Three positive cases were identified as Mycobacterium avium and the remaining M. tuberculosis (one case could not be identified). CONCLUSION: MBC can be a valuable additional method to diagnose TB, particularly in immunosuppressed HIV patients when sputum cannot be collected.